European memory in populism
1 online resource.
Keywords: "European Memory in Populism explores the links between memory, heritage and populism in contemporary Europe and beyond. Focusing on circulating ideas of memory, especially European memory, in contemporary populist discourses, the book also analyses populist ideas in sites and practices of remembrance that usually tend to go unnoticed. More broadly, the theoretical heart of the book reflects upon the similarities, differences, and slippages between memory, populism, nationalism, and cultural racism and the ways in which social memory and heritage contributes to give substance to various ideas of what constitutes the 'people' in populist discourse and beyond. Bringing together a group of political scientists, anthropologists, and cultural and memory studies scholars, the book illuminates the relationship between memory and populism from different angles and in different contexts. The contributors to the volume discuss dominant notions of European heritage that circulate in the public sphere and in political discourse, and consider how the politics of fear relates to such notions of European heritage and identity across Europe and the European Union. Ultimately, this volume will shed light on how notions of a shared European heritage and memory can be used not only to include and connect Europeans, but also to exclude some of them. Investigating the ways in which nationalist populist forces mobilize the idea of a shared, homogeneous European civilization, European Memory in Populism will be of interest to scholars and students in the fields of European studies, memory and heritage studies, migration studies, anthropology, political science and sociology"--